MONICA-undersökningen i norra Sverige 2004 - Söderberg, Stefan; Forslund, Ann-Sofie (Swedish National Data Service, 2012)
The Northern Sweden MONICA Study started with the WHO MONICA Study in 1985. The purpose was to monitor trends in mortality and morbidity in cardiovascular disease and relate them to trends in risk factors. Since 1985 21,000 strictly validated stroke events and 18,000 myocardial infarctions have been included in two registers. During the same period, six population based surveys have been taking place, the latest in 2009. The participation rates have been 69-81%. Subjects donated samples to the Northern Sweden Biobank. After 25 years since the start of the study, participants are starting to suffer from stroke, infarctions and diabetes in a rapidly increasing rate. We have successfully matched the event registers with population survey data, thereby creating a cost-effective prospective study design for MI, stroke and diabetes. Data from the three data bases has been used in more than 85 original studies and 14 dissertations since 2007. Increasingly other fields have been explored such as infectious diseases, nutrion and enviromental toxins. Purpose: To study cardiovascular risk factors in the population and the incidence of myocardial infarction and stroke after strict validation. A randomised sample of 2500 persons in ages 25-74 were invited to participate in the 1986 study. Sedan 1985 har MONICA-undersökningen i Norr- och Västerbotten registrerat insjuknande i slaganfall och hjärtinfarkt samt genomfört hälsoundersökningar av befolkningen. MONICA står för Multinational MONItoring of trends and determinants in CArdiovascular disease. Över 18000 hjärtinfarkter och 21000 fall av stroke har registrerats sedan 1985. Samtliga fall inklusive dem som avlider innan sjukhusvård i åldrarna 25 till 74 har inkluderats enligt strikta och över tid ensartade WHO kriterier efter validering mot journaldata Sedan 1986 har det genomförts sju undersökningar av ett slumpmässigt urval av befolkningen avseende bl.a. riskfaktorer för hjärtkärlsjukdom och diabetes, omfattande totalt cirka 12000 individer. Deltagarfrekvensen har ...